Progesterone Suppresses Neisseria gonorrhoeae-Induced Inflammation Through Inhibition of NLRP3 Inflammasome Pathway in THP-1 Cells and Murine Models - Zhang, Song; Zhang, Yingmiao; Gan, Lu; Wei, Fen; Chai, Bao; A Aljaafreh, Amaneh Abdel Hafez; Liu, Xinxin; Duan, Xiaoru; Jiang, Jian; Wang, Xin; He, Mengwen; Huang, Xian; et al. (Frontiers in Microbiology, 2021)
Asymptomatic/subclinical gonococcal infections in females continue to be prevalent within the general population, thus emerging as a global health problem. However, the reasons for these clinical manifestations are unknown. Our group had previously found out that in females, asymptomatic gonococcal infections correlate with higher serum progesterone (P4) levels and lower IL-1β levels in cervical secretions. We used murine infection model and THP-1 cells to determine whether P4 exerts anti-inflammatory effects on gonococcal infections. In the murine infection model, P4 (1 mg/day) inhibited the inflammatory effects induced by gonococcal infections which led to decreased neutrophil infiltration, reduced polymorphonuclear neutrophils (PMNs) numbers, IL-1β, TNF-α, and IL-6 levels in vaginal secretions. In addition, P4 down-regulated the mRNA and protein levels of NLRP3, associated with lower mRNA levels of pro-IL-1β, repressed caspase-1 activity in genital tissues and THP-1 cells. Moreover, P4 suppressed the phosphorylation levels of NF-κB and attenuated Neisseria gonorrhoeae (N. gonorrhoeae, gonococci or GC)-induced ROS generation. This is consistent with the two signals required for activation of the NLRP3 (NOD-, LRR-, and pyrin domain-containing protein 3) inflammasome. In conclusion, our result shows that P4 suppresses the gonococci induced-inflammation, especially through the NLRP3 inflammasome pathway, and partially explains the pathogenesis of asymptomatic GC infection in women.